E and P Selectins Are Not Required for Resistance to Severe Murine Lyme Arthritis - Seiler, Kathleen Petri (American Society for Microbiology, 1998)
Borrelia burgdorferi-induced arthritis in mice is characterized by tendonitis, synovitis, and inflammatory-cell infiltrate, predominantly of neutrophils. Because genetic deficiency in E and P selectins results in delayed recruitment of neutrophils to sites of inflammation, mice with this deficiency were tested for their response to infection with B. burgdorferi. E and P selectins were not required for the control of B. burgdorferi numbers, nor did deficiency in E and P selectins result in alteration of arthritis severity.